Enhanced Thrombin Formation in Patients With Ventricular Assist Devices Experiencing Bleeding: Insights From the Multicenter PREVENT Study. Issue 3 (8th September 2022) - Jeske, Walter; Ransom, John; Katz, Jason N.; Kilic, Ahmet; Lindenfeld, Joann; Egnaczyk, Gregory; Shah, Palak; Brieke, Andreas; Uriel, Nir; Crandall, Daniel; Farrar, David J.; Walenga, Jeanine M.
Abstract : The aim of this investigation was to characterize the hemostatic status of heart failure patients with implanted left ventricular assist devices (LVADs) to propose a mechanism associated with bleeding. Patients (n = 300) from 23 US hospitals were enrolled in the PREVENtion of HeartMate II Pump Thrombosis through Clinical Management (PREVENT) study. A biobank was established with serum and plasma samples prospectively collected from a cohort of 175 patients preimplant baseline (BL) and 3 months (3M) postimplant. Outcomes were collected for 6 months. Thrombin (prothrombin fragment 1.2 [F1.2], functional thrombin generation [TG]) and fibrinolytic activity (D-dimer, plasminogen activator inhibitor-1 [PAI-1]), but not contact activation (complement C5a), were elevated in heart failure patients at BL. F1.2, TG, and PAI-1 levels decreased 3M after LVAD implantation ( p < 0.01) but did not revert to normal in all patients; conversely, D-dimer increased BL to 3M ( p < 0.01). Compared with patients without events, thrombin activity (F1.2) was increased in patients with late bleeding (3–4 months postimplant) ( p = 0.06) and in those with late gastrointestinal (GI) bleeding ( p = 0.01). Patients with 3M F1.2 levels above the cohort mean had a higher incidence of bleeding ( p < 0.001) and GI bleeding ( p < 0.001) compared with those with below mean F1.2. Patients experiencing multiple bleeding events were more likely to have 3M F1.2 greater than the cohort mean. Despite anticoagulation with aspirin and warfarin, LVAD implanted patients exhibit hemostatic activation. Excess thrombin formation, particularly shown by increased F1.2, was demonstrated in association with bleeding in LVAD implanted patients.